Sposoby wykorzystania napisów scenicznych jako metody przekładu spektakli teatralnych w trakcie Malta Festival Poznań 2017 - Czubińska, Małgorzata (Investigationes Linguisticae, 2019)
As a result of the internationalization of theatrical art and the development of modern technologies, surtitles are currently one of the most frequently used methods of theater translation. The diversity of solutions currently proposed by theaters around the world entails the necessity of development of the common rules of the creation of surtitles. This role is to be fulfilled by the French rulebook prepared by the by the drama institute Maison Antoine Vitez, entitled "Guide du sur-titrage au théâtre" (Bataillon, Muhleisen, Diez, 2016). The following analysis is based on examples of the use of surtitles from four performances presented during the Malta Festival 2017 in Poznań. Its purpose will be to answer the question: to what extent the surtitles used during the Polish festival of theater are in compliance with the norms suggested by authors of“Guide du sur-titrage au théâtre” (2016)?